An experimental study on structural performance of U-shaped shear connector in composite cold-formed steel floor joists. (15th December 2021) - Hosseinpour, Mahmoud; Zeynalian, Mehran; Ataei, Abdoreza; Daei, Maryam
Highlights: Performance of U-shaped shear connectors in CFS-concrete composite beam is studied. 10 full scale push-out tests are conducted to study the U-shaped shear connectors. Four types of shear connectors were considered.· Two types of CFS beams with thickness of 1 and 2 mm are taken into account. Ductility of the shear connectors is examined according to EC4 code. Abstract: Since few studies have focused on the shear connectors in the composite cold-formed steel beams so far, this paper studies the behavior of the U-shaped shear connectors which can be used in the composite beams comprising cold-formed steel beam and concrete slab. Accordingly, ten full scale push-out tests were conducted to investigate the ultimate load, failure modes, ductility and stiffness of the U-shaped shear connectors. For this purpose, four types of shear connectors by different screw diameters and orientation of U-shaped shear connectors with respect to the direction of the load were considered; and utilized by two types of cold-formed steel beams with thickness of 1 and 2 mm. The results have shown that change of the screws' diameter from 4.8 to 6.3 mm, leads to an increase of the ultimate load about 25% and 40% for 1 mm and 2 mm thick specimens, respectively. It is also concluded that transverse shear connectors have a better performance than longitudinal ones considering both ultimate load and ductility. The main observed failure mode of all specimens was tilting and bearing in shear connectors except for two specimens which was incorporated with pull-over mode. Moreover, ductility of the shear connectors was examined according to EC4 code. The results show that except for two specimens, the other U-shaped shear connectors used in this study can be accounted ductile.